Melatonin reduces LH, 17 beta-estradiol and induces differential regulation of sex steroid receptors in reproductive tissues during rat ovulation - Pinheiro Patrícia Fernanda F; Fioruci Beatriz A; Mendes Leonardo O; Amorim João PA; Teixeira Giovana R; Fávaro Wagner; Seiva Fábio RF; A Chuffa Luiz Gustavo; Fernandes Ana Angélica H; Franci Janete AA; Delella Flávia K; Martinez Marcelo; et al. (BMC, 2011)
Abstract Background Melatonin is associated with direct or indirect actions upon female reproductive function. However, its effects on sex hormones and steroid receptors during ovulation are not clearly defined. This study aimed to verify whether exposure to long-term melatonin is able to cause reproductive hormonal disturbances as well as their role on sex steroid receptors in the rat ovary, oviduct and uterus during ovulation. Methods Twenty-four adult Wistar rats, 60 days old (+/- 250 g) were randomly divided into two groups. Control group (Co): received 0.9% NaCl 0.3 mL + 95% ethanol 0.04 mL as vehicle; Melatonin-treated group (MEL): received vehicle + melatonin [100 μg/100 g BW/day] both intraperitoneally during 60 days. All animals were euthanized by decapitation during the morning estrus at 4 a.m. Results Melatonin significantly reduced the plasma levels of LH and 17 beta-estradiol, while urinary 6-sulfatoximelatonin (STM) was increased at the morning estrus. In addition, melatonin promoted differential regulation of the estrogen receptor (ER), progesterone receptor (PR), androgen receptor (AR) and melatonin receptor (MTR) along the reproductive tissues. In ovary, melatonin induced a down-regulation of ER-alpha and PRB levels. Conversely, it was observed that PRA and MT1R were up-regulated. In oviduct, AR and ER-alpha levels were down-regulated, in contrast to high expression of both PRA and PRB. Finally, the ER-beta and PRB levels were down-regulated in uterus tissue and only MT1R was up-regulated. Conclusions We suggest that melatonin partially suppress the hypothalamus-pituitary-ovarian axis, in addition, it induces differential regulation of sex steroid receptors in the ovary, oviduct and uterus during ovulation.